Infographics : a journalist's guide - Stovall, James Glen. 4 0 16; 5 (Boston : Allyn and Bacon, 1997)
Presents information about different graphic forms, inlcuding charts, maps, and illustrations, and discusses how journalists can use them properly in communication activities.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; Illustrations.;Illustrations. -- Newspapers;Charts, diagrams, etc.;Newspapers;Charts, diagrams, etc; 20; 2